Registration of 'Purple Bounty' and 'Purple Prosperity' hairy vetch. Issue 3 (16th September 2020) - Moore, Virginia Mae; Maul, Jude E.; Wilson, Dave; Curran, William S.; Brainard, Daniel C.; Devine, Thomas E.; Mirsky, Steven B.
Abstract: The hairy vetch ( Vicia villosa Roth) cultivars 'Purple Bounty' (Reg. no. CV‐12, PI 648342) and 'Purple Prosperity' (Reg. no. CV‐11, PI 654047) were released in 2007 and 2008, respectively, by the USDA–ARS in collaboration with the Rodale Institute and the agricultural experiment stations of Pennsylvania State University and Cornell University. Hairy vetch is a commonly used annual legume cover crop grown for its cold tolerance, fast growth, large biomass production, and ability to fix N2 . However, this species has not been selected for the traits needed to optimize its use as a cover crop. Our breeding program focused on developing a cultivar that was both early flowering and had adequate winter survival and therefore adapted to mechanical termination in organic no‐till production in the U.S. Northeast and Mid‐Atlantic. Purple Bounty and Purple Prosperity were developed between 1998 and 2005 using recurrent selection at nurseries in Beltsville and Keedysville, MD. In 2005–2006, selections were evaluated against commercial checks for flowering time in Maryland and Pennsylvania, and in the 2006–2007 and 2007–2008 seasons they were evaluated in 10 locations (12 total site‐years) across the United States for winter survival. Purple Bounty and Purple Prosperity both flowered earlier than the commercial material against which they were tested (significance depended on the date and site); Purple Bounty was the earlier flowering of the two cultivars. Purple Bounty and Purple Prosperity also had equivalent or improved winter survival compared with 'AU Early Cover', an early‐maturing cultivar developed in the southern United States, at all test locations. Purple Prosperity is no longer commercially available, but Purple Bounty is currently licensed and distributed by Allied Seed (Nampa, ID).